Biological and molecular characterization of a Tospovirus isolate from tomato and its relationship with other Tospoviruses - A.I. BHAT and Y.S. AHLAWAT, K. UMAMAHESWARAN, R.K. JAIN*, (Indian Phytopathology, 2003)
A Tospovirus was isolated from tomato (Lycopersicon esculentum Mill) plants showing severe necrosis of leaves and growing buds. Host range studies indicated that the tomato Tospovirus isolate was closely related to Groundnut bud necrosis virus (GBNV). Sequence analyses of nucleocapsid protein (N) gene showed that the amino acid sequence identity with GBNV was 96% while the identities with other Tospoviruses were in the range of 16-85%. On this basis, it is concluded that the tomato Tospovirus should be considered as a strain of GBNV and designated as GBNV-To.